Subclinical mastitis in small-scale dairy farms under grazing or in total confinement in the central highlands of Mexico - Valle-Aguilar, Mariana; López-González, Felipe; Sainz-Ramírez, Aurora; Arriaga-Jordan, Carlos Manuel (Indian Journal of Dairy Science, 2020)
Mastitis is the most frequent disease in dairy farms worldwide, causing severe economic loss; being subclinical mastitis the most important as it is a silent disease. The objective of this work was to compare the udder health status in cows under limited grazing against cows in total confinement in small-scale dairy systems. Ten small-scale dairy farms participated in the study, with five farms that had implemented grazing of their pastures and five farms that continued the conventional management of total confinement of their herds and feeding based in cut-and-carry pasture, straws, agricultural by products, and concentrates. The highest yielding five cows from each farm were selected for the study. The California Mastitis Test (CMT) performed every 2 weeks, from June 17 to July 15 on all participating cows, and Somatic cell counts (SCC) was determined on the farm pooled milk. Results for CMT were subjected to a Chi-squared test, and SCC to analysis of variance after log10 transformation. There were significant differences both for CMT and SCC with lower values for cows under restricted grazing than in total confinement. Restricted grazing of dairy cows in small-scale dairy systems result in better udder health, and therefore better quality milk.